Higher contact force during radiofrequency ablation leads to a much larger increase in edema as compared to chronic lesion size. (6th June 2018) - Thomas, Samuel; Silvernagel, Josh; Angel, Nathan; Kholmovski, Eugene; Ghafoori, Elyar; Hu, Nan; Ashton, John; Dosdall, Derek J.; MacLeod, Rob; Ranjan, Ravi
Abstract: Introduction: Reversible edema is a part of any radiofrequency ablation but its relationship with contact force is unknown. The goal of this study was to characterize through histology and MRI, acute and chronic ablation lesions and reversible edema with contact force. Methods and results: In a canine model (n = 14), chronic ventricular lesions were created with a 3.5‐mm tip ThermoCool SmartTouch (Biosense Webster) catheter at 25 W or 40 W for 30 seconds. Repeat ablation was performed after 3 months to create a second set of lesions (acute). Each ablation procedure was followed by in vivo T2‐weighted MRI for edema and late‐gadolinium enhancement (LGE) MRI for lesion characterization. For chronic lesions, the mean scar volumes at 25 W and 40 W were 77.8 ± 34.5 mm 3 (n = 24) and 139.1 ± 69.7 mm 3 (n = 12), respectively. The volume of chronic lesions increased (25 W: P < 0.001, 40 W: P < 0.001) with greater contact force. For acute lesions, the mean volumes of the lesion were 286.0 ± 129.8 mm 3 (n = 19) and 422.1 ± 113.1 mm 3 (n = 16) for 25 W and 40 W, respectively (P < 0.001 compared to chronic scar). On T2‐weighted MRI, the acute edema volume was on average 5.6–8.7 times higher than the acute lesion volume and increased with contact force (25 W: P = 0.001, 40 W: P = 0.011). Conclusion: With increasing contact force, there is a marginal increase in lesion size but accompanied with a significantly larger edema. The reversible edema that is much larger than the chronic lesion volume may explain some of the chronic procedure failures.